The social character of secondary industry in South Africa, 1915-1945. (With special reference to the Witwatersrand) - Freund, Bill (My University, 1985)
There can be little dispute about the significance and historic importance of the rise of South African secondary industry. Nonetheless, and despite the ready availability of general considerations, fundamental aspects of its development have received little attention, if any, in the historical literature. This essay means to call attention to some of those aspects in the earlier phases of South African industrial development ending with the Second World War. The main focus will be on the forms and allocation of labour, an area which has been relatively neglected and the one that allows for an examination of economic changes through the historically specific character of South African society. The distinctive and extremely heterogeneous workforce of the first half of this century in secondary industry stands apart both from sectors of the economy developed earlier and from the industrial labour force structure that would follow.
African Studies Seminar series. Paper presented 22 April, 1985
Keywords: Labor supply. South Africa. History. 20th century